Titanium-silicon homogeneous polyester catalyst as well as preparation method and application thereof

By using titanium-silicon homogeneous polyester catalysts to prepare titanium-silicon homogeneous polyester catalysts using titanium compounds, silicon compounds and specific organophosphide ligands, the problem of poor stability and yellowing of titanium-based catalysts in polyester synthesis is solved, and the effect of improving catalytic activity and stability is achieved.

CN119684352APending Publication Date: 2025-03-25CHINA RESOURCES PACKAGING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411843192.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Titanium-based catalysts have poor stability, yellowing and turbidity in the polyester synthesis process, which limits their large-scale promotion and use.

Method used

Titanium silicon homogeneous polyester catalyst is prepared using titanium compounds, silicon compounds and specific organophosphide ligands to improve catalytic activity and stereoselectivity by optimizing the steric hindrance and electronic effects of the ligand.

Benefits of technology

The yellowing problem of titanium-based catalyst polyester products is improved, the stability and activity of the catalyst are improved, and the adverse effects of phosphate-based phosphides on the catalyst and reaction are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684352A_ABST
    Figure CN119684352A_ABST
Patent Text Reader

Abstract

The invention provides a titanium-silicon homogeneous polyester catalyst as well as a preparation method and application thereof, and relates to the technical field of polyester synthesis. The titanium-silicon homogeneous polyester catalyst is mainly prepared from a titanium compound, a silicon compound and an organic phosphine ligand as shown in a formula (I). The polyester catalyst can optimize the steric hindrance and electron effect of substituent groups through selection of novel organic phosphorus ligands, improve the catalytic activity and stereoselectivity of the catalyst, improve the yellowing problem of a titanium catalyst polyester product to a certain extent, and relieve the problems of instability and poor stability of a titanium catalyst in the prior art. And the color becomes dark after illumination. Meanwhile, the catalyst ligand provided by the invention can also improve the action capacity and hydrolysis resistance of the active component Ti, and avoid the adverse effects of phosphate phosphinates on the catalyst and subsequent reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester synthesis, in particular to a titanium silicon homogeneous polyester catalyst and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (hereinafter referred to as polyester PET) has many advantages, such as good transparency, non-toxicity, anti-permeability, light weight, creep resistance, fatigue resistance, good friction resistance, the greatest toughness among thermoplastics, good electrical insulation properties, and better processing properties. It has become the variety with the largest production capacity in the chemical fiber field and is widely used in fiber, film, sheet, bottle and other application materials.

[0003] Catalysts have always been regarded as the core technology of polyester synthesis, playing a crucial and decisive role in promoting product performance improvement and process innovation. At present, in the industrialized polyester production at home and abroad, the catalysts are mainly antimony, germanium and titanium. Among them, antimony catalysts (including antimony trioxide, antimony acetate and ethylene glycol antimony, etc.) are the most commonly used. About 90% of the world's polyester is produced by antimony catalysts, but antimony is a heavy metal element with certain toxicity, which will bring certain life and health problems and environmental pollution problems, which to a certain extent limits the use of antimony catalysts. The reaction activity of germanium catalysts is moderate, there are fewer side reactions during the reaction process, and the polyester produced has good color, but due to the influence of factors such as scarce resources and strategic control, it is expensive and has shown an increasing trend year by year, greatly increasing the production cost of polyester products.

[0004] Titanium-based catalysts have always been the focus of scientific research institutions and production companies due to their many advantages such as high catalytic activity, no heavy metals, non-toxicity, green environmental protection, abundant reserves and low cost. However, as a polyester synthesis application field, titanium-based catalyst polyester products have always had practical problems such as poor stability, yellowing and turbidity of products, which greatly hindered and restricted their large-scale promotion and use.

[0005] The specific reason is that titanium catalysts have high activity and poor selectivity compared to antimony catalysts, which leads to yellowing of polyester produced by titanium catalysts. During the synthesis of polyester catalyzed by titanium catalysts, thermal degradation and thermal oxidation degradation side reactions occur: (1) Acetaldehyde is produced, and titanium catalysts have high activity and poor selectivity. They will combine with carbonyl groups to accelerate the condensation of acetaldehyde to form conjugated compounds; (2) Hydroxylation occurs on the benzene ring, and the titanium catalyst participates in the oxidation reaction to convert the phenolic hydroxyl group into a quinone-type compound.

[0006] At present, the most common solutions are mainly the following: 1. Adding reaction aids to reduce the activity of titanium catalysts to solve the yellowing problem. The most commonly used method is to add phosphate aids, but this method not only increases the material addition process in the production process, the amount of addition is difficult to control and evenly disperse, and at the same time greatly reduces the binding effect of the aid during the reaction process, greatly increases the amount of aid, and increases the difficulty of controlling the reaction process; 2. Using organic phosphates, aminophosphonic acid compounds, and organic metal salts to modify and optimize the catalyst, but this type of improvement will not only introduce metal elements such as Na, Mg, A1, and Zn, but the synthesis process also involves the generation of many small molecular groups such as acetate, fatty alcohol, and phenyl alcohol, which are difficult to successfully remove from the catalyst later, which will affect the catalyst activity, and then have varying degrees of impact on the final polyester product quality and subsequent processing performance.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The first purpose of the present invention is to provide a titanium-silicon homogeneous polyester catalyst, which improves the yellowing problem of titanium-based catalyst polyester products to a certain extent through the selection of a new type of organic phosphorus ligand structure, and can also improve the action ability of the active component Ti, avoiding the adverse effects of phosphate phosphides on the catalyst and subsequent reactions.

[0009] The second object of the present invention is to provide a method for preparing a titanium silicon homogeneous polyester catalyst.

[0010] The third object of the present invention is to provide an application of a titanium-silicon homogeneous polyester catalyst.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] The present invention provides a titanium-silicon homogeneous polyester catalyst, which is mainly prepared from a titanium compound, a silicon compound and an organic phosphide ligand of formula (I);

[0013]

[0014] In formula (I), R, R', and R" are independently one of -OH, -COOH, -PO3H2, -NO2, -NH2, -SO3H, -H, -H2C-COOH, -H2C-NH2, -H2C-PO3H2, a monocyclic aromatic hydrocarbon group, and a C1-C6 alkane chain structure, and n is an integer of 1 to 8;

[0015] The monocyclic aromatic hydrocarbon groups include: One of;

[0016] In the monocyclic aromatic hydrocarbon group, R1 to R5 are independently one of —OH, —COOH, —PO3H2, —NO2, —NH2, —SO3H, —H, —H2C-COOH, —H2C-NH2, —H2C-PO3H2, a monocyclic aromatic hydrocarbon group and a C1-C6 alkane chain structure.

[0017] Furthermore, the organic phosphide ligand is at least one of 1-hydroxyethylidene-1,1-diphosphonic acid, 1-hydroxybutylidene-1,1-diphosphonic acid, 1-hydroxypropylidene-1,1-diphosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 3-phosphopropionic acid, and (4-hydroxybenzyl)phosphonic acid.

[0018] Furthermore, the titanium compound is a tetraalkyl titanate, and the alkyl ester contained in the tetraalkyl titanate is a C1-C7 alkyl;

[0019] Preferably, the tetraalkyl titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.

[0020] Furthermore, the silicon compound is at least one of ethyl orthosilicate, tetraisopropyl orthosilicate, and tetra-n-propyl orthosilicate.

[0021] The present invention provides a method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0022] (A) providing a titanium compound solution, a silicon compound solution and an organic phosphide ligand solution;

[0023] (B) adding the organic phosphide ligand solution to the titanium compound solution to react and obtain reaction product I;

[0024] (C) adding the silicon compound solution to the reaction product I to obtain the reaction product II, and removing the small molecules to obtain the titanium silicon homogeneous polyester catalyst.

[0025] Furthermore, the mass ratio of the titanium compound to the solvent in the titanium compound solution is 1:0.5-50;

[0026] And / or, the mass ratio of the silicon compound to the solvent in the silicon compound solution is 1:0.5-30;

[0027] And / or, the mass ratio of the organic phosphide ligand to the solvent in the organic phosphide ligand solution is 1:0.5-50.

[0028] Furthermore, during the preparation of the reaction product I, the molar ratio of the titanium compound to the organic phosphide ligand is 1:0.1-10.

[0029] Furthermore, during the preparation of the reaction product II, the molar ratio of the titanium compound to the silicon compound is 20 to 1:1.

[0030] Furthermore, the reaction temperature of step (B) is 50-120°C and the reaction time is 0.5-4h;

[0031] The reaction temperature of step (C) is 50-120° C. and the reaction time is 0.5-4 h.

[0032] The invention provides an application of a titanium silicon homogeneous polyester catalyst in catalytic preparation of polyethylene terephthalate and copolyester thereof.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The titanium-silicon homogeneous polyester catalyst provided by the present invention is mainly prepared from a titanium compound, a silicon compound and an organic phosphide ligand of formula (I). The polyester catalyst can optimize the steric hindrance and electronic effect of the substituent through the selection of a novel organic phosphorus ligand structure, improve the catalytic activity and stereoselectivity of the catalyst, improve the yellowing problem of titanium-based catalyst polyester products to a certain extent, and alleviate the practical dilemma that titanium-based catalysts in the prior art are unstable and darken in color after exposure to light. At the same time, the catalyst ligand of the present application can also improve the action ability of the active component Ti and its anti-hydrolysis performance, avoiding the adverse effects of phosphate phosphides on the catalyst and subsequent reactions.

[0035] In addition, the present application avoids the problem of the existing titanium silicon-based liquid homogeneous polyester catalyst introducing many reactants such as acetates, phosphates, etc. such as Na, Mg, Al, Zn, and La, and improves the catalyst stability, the quality of the final polyester product, and the processing performance to varying degrees.

[0036] The titanium silicon homogeneous polyester catalyst provided by the invention can be widely used in the catalytic preparation process of polyethylene terephthalate. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is the infrared spectrum of the titanium silicon homogeneous polyester catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] According to one aspect of the present invention, a titanium-silicon homogeneous polyester catalyst is prepared mainly from a titanium compound, a silicon compound and an organic phosphide ligand of formula (I);

[0041]

[0042] In formula (I), R, R', and R" are independently one of -OH, -COOH, -PO3H2, -NO2, -NH2, -SO3H, -H, -H2C-COOH, -H2C-NH2, -H2C-PO3H2, a monocyclic aromatic hydrocarbon group, and a C1-C6 alkane chain structure, and n is an integer of 1 to 8;

[0043] The monocyclic aromatic hydrocarbon groups include: One of;

[0044] In the monocyclic aromatic hydrocarbon group, R1 to R5 are independently one of —OH, —COOH, —PO3H2, —NO2, —NH2, —SO3H, —H, —H2C-COOH, —H2C-NH2, —H2C-PO3H2, a monocyclic aromatic hydrocarbon group and a C1-C6 alkane chain structure.

[0045] It should be noted that for catalysts with metal elements as catalytic active centers, the catalytic performance is mainly determined by the atomic radius, electronegativity, electronic effect of the ligand and steric hindrance of the metal. Among them, the steric hindrance and electronic effect of the ligand substituent have a great influence on the catalytic activity and stereoselectivity of the catalyst. Generally, by changing the electronic effect and steric hindrance of the ligand, the side reactions of the catalyst can be reduced and its stereoselectivity can be improved.

[0046] Based on the above principle, the titanium-silicon homogeneous polyester catalyst provided by the present invention is mainly prepared from a titanium compound, a silicon compound and an organic phosphide ligand of formula (I). The polyester catalyst of the present application can optimize the steric hindrance and electronic effect of the substituent through the selection of a new organic phosphorus ligand structure, enhance the catalytic activity and stereoselectivity of the catalyst, and improve the yellowing problem of titanium-based catalyst polyester products to a certain extent, while overcoming the practical dilemma that titanium-based catalysts in the prior art are unstable and darken in color after exposure to light. At the same time, the catalyst ligand of the present application can also improve the action ability of the active component Ti, as well as the anti-hydrolysis performance, and avoid the adverse effects of phosphate phosphides on the catalyst and subsequent reactions.

[0047] In addition, the present application avoids the problem of the existing titanium silicon-based liquid homogeneous polyester catalyst introducing many reactants such as acetates, phosphates, etc. such as Na, Mg, Al, Zn, and La, and improves the catalyst stability, the quality of the final polyester product, and the processing performance to varying degrees.

[0048] The organic phosphine ligand is at least one of 1-hydroxyethylidene-1,1-diphosphonic acid, 1-hydroxybutylidene-1,1-diphosphonic acid, 1-hydroxypropylidene-1,1-diphosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 3-phosphopropionic acid, and (4-hydroxybenzyl)phosphonic acid.

[0049] In a preferred embodiment of the present invention, the titanium compound is a tetraalkyl titanate, and the alkyl ester contained in the tetraalkyl titanate is a C1-C7 alkyl group;

[0050] Preferably, the tetraalkyl titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.

[0051] In a preferred embodiment of the present invention, the silicon compound is at least one of ethyl orthosilicate, tetraisopropyl orthosilicate, and tetra-n-propyl orthosilicate.

[0052] According to one aspect of the present invention, a method for preparing a titanium-silicon homogeneous polyester catalyst comprises:

[0053] (A) providing a titanium compound solution, a silicon compound solution and an organic phosphide ligand solution;

[0054] (B) adding the organic phosphide ligand solution to the titanium compound solution, stirring and reacting to prepare a reaction product I;

[0055] (C) adding the silicon compound solution to the reaction product I, stirring the reaction to obtain the reaction product II, and removing the small molecules to obtain the titanium silicon homogeneous polyester catalyst.

[0056] The present invention provides a method for preparing a titanium-silicon homogeneous polyester catalyst, wherein the method comprises: firstly adding an organic phosphide ligand solution to a titanium compound solution to prepare a reaction product I, then adding a silicon compound solution to the reaction product I to prepare a reaction product II, and removing small molecules to obtain a titanium-silicon homogeneous polyester catalyst. The method for preparing a titanium-silicon homogeneous polyester catalyst of the present application has the technical advantages of simple preparation process and easy operation.

[0057] It should be noted that existing traditional titanate catalysts, such as titanium isopropoxide, tetrabutyl titanate, etc., are very easy to react with water under water or high temperature conditions (especially in the high-temperature polyester catalytic synthesis process). The titanate reacts with water very easily and undergoes hydrolysis reaction to generate TiO2, which seriously affects the performance of the catalyst and product quality.

[0058] The specific titanate hydrolysis reaction process is as follows:

[0059]

[0060] In addition, the existing pure titanium silicon catalyst has a structural form of a Ti-O-Si macromolecular form, but the Ti-O-Si macromolecular form has poor water solubility and even generates a heterogeneous solid catalyst, which directly leads to reduced dispersion performance of the catalyst and poor polymerization stability.

[0061] The structure of the organic phosphine ligand of the present application is rich in -OH, C=O, P=O, P-OH and other groups that can react with Ti and Si elements to form a complex and coordinate reaction, thereby achieving the complex and coordinate effect on the titanium compound and silicon compound of the present application. The catalyst finally prepared by the present application has a stable complex morphology and a homogeneous effect, which not only improves the stability of the catalyst during the polymerization process at a high temperature, but also the introduction of polar groups enhances the ability of the catalyst to interact with water, can form a stable system, and improve the anti-hydrolysis performance of the catalyst.

[0062] In a preferred embodiment of the present invention, the mass ratio of the titanium compound to the solvent in the titanium compound solution is 1:0.5-50;

[0063] In a preferred embodiment of the present invention, the mass ratio of the silicon compound to the solvent in the silicon compound solution is 1:0.5-30;

[0064] In a preferred embodiment of the present invention, the mass ratio of the organic phosphide ligand to the solvent in the organic phosphide ligand solution is 1:0.5-50.

[0065] In a preferred embodiment of the present invention, during the preparation of the reaction product I, the molar ratio of the titanium compound to the organic phosphide ligand is 1:0.1-10.

[0066] In a preferred embodiment of the present invention, during the preparation of the reaction product II, the molar ratio of the titanium compound to the silicon compound is 20 to 1:1.

[0067] In a preferred embodiment of the present invention, the reaction temperature of step (B) is 50-120° C. and the reaction time is 0.5-4 h;

[0068] In a preferred embodiment of the present invention, the reaction temperature of step (C) is 50-120° C. and the reaction time is 0.5-4 h.

[0069] According to one aspect of the present invention, a titanium-silicon homogeneous polyester catalyst is used in the catalytic preparation of polyethylene terephthalate and its copolyester.

[0070] The invention provides a method for preparing polyethylene terephthalate in a catalytic process.

[0071] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0072] Example 1

[0073] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0074] 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added to a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser. Under mechanical stirring, 81.04 g of 2-phosphonobutane-1,2,4-tricarboxylic acid (0.3 mol) solution (100 g of water) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for 2 h. After the reaction was completed, the temperature was lowered to room temperature, and 3.12 g of tetraethyl orthosilicate (0.015 mol) solution (50 g of anhydrous ethanol) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst A.

[0075] Figure 1 This is the infrared spectrum of the titanium silicon homogeneous polyester catalyst prepared in Example 1 of the present invention.

[0076] Example 2

[0077] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0078] To a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser, 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added. Under mechanical stirring, 81.04 g of 2-phosphonobutane-1,2,4-tricarboxylic acid (0.3 mol) solution (100 g of anhydrous ethanol) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for reaction for 2 h. After the reaction was completed, the temperature was lowered to room temperature. 1.56 g of tetraethyl orthosilicate (0.0075 mol) solution (50 g of anhydrous ethanol) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst B.

[0079] Example 3

[0080] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0081] 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added to a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser. Under mechanical stirring, 121.56 g of 2-phosphonobutane-1,2,4-tricarboxylic acid (0.45 mol) solution (100 g of anhydrous ethanol) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100° C. for reaction for 2 h. After the reaction was completed, the temperature was lowered to room temperature. 1.56 g of tetraethyl orthosilicate (0.0075 mol) solution (50 g of anhydrous ethanol) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst C.

[0082] Example 4

[0083] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0084] To a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser, 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added. Under mechanical stirring, 46.20 g of 3-phosphopropionic acid (0.3 mol) solution (100 g of anhydrous ethanol) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for 1 h. After the reaction was completed, the temperature was lowered to room temperature. 3.12 g of tetraethyl orthosilicate (0.015 mol) solution (50 g of anhydrous ethanol) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst D.

[0085] Example 5

[0086] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0087] To a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser, 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added. Under mechanical stirring, 46.20 g of 3-phosphopropionic acid (0.3 mol) solution (100 g of water) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for reaction for h. After the reaction was completed, the temperature was lowered to room temperature. 1.56 g of tetraethyl orthosilicate (0.0075 mol) solution (50 g of water) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst E.

[0088] Example 6

[0089] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0090] To a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser, 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added. Under mechanical stirring, 56.44 g of 4-hydroxybenzylphosphonic acid solution (100 g of anhydrous ethanol) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for reaction for h. After the reaction was completed, the temperature was lowered to room temperature. 1.56 g of tetraethyl orthosilicate (0.0075 mol) solution (50 g of water) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst F.

[0091] Example 7

[0092] A method for preparing a titanium-silicon homogeneous polyester catalyst, the preparation method comprising:

[0093] To a temperature-controlled reactor equipped with a stirrer, a separating funnel and a condenser, 42.64 g of tetraisopropyl titanate (0.15 mol) ethanol solution (50 g of anhydrous ethanol) was added. Under mechanical stirring, 81.04 g of 2-phosphonobutane-1,2,4-tricarboxylic acid (0.3 mol) solution (100 g of water) was slowly dripped into the reactor. After the addition was completed, the temperature was raised to 100 ° C for 1 h. After the reaction was completed, the temperature was lowered to room temperature. 6.44 g of tetraethyl orthosilicate (0.03 mol) solution (50 g of anhydrous ethanol) was slowly dripped into the reactor. The reaction was continued to stir at room temperature for 2 h. After the reaction was completed, the small molecules were removed to obtain polyester catalyst G.

[0094] Experimental Example 1

[0095] The 7 titanium catalysts A, B, C, D, E, F, and G prepared in Examples 1 to 7 above were used to evaluate the PET polycondensation activity and the color of the final product, and tetrabutyl titanate was used as a catalyst to conduct a control experiment as a comparative example. The specific experimental steps are as follows:

[0096] After slurrying, terephthalic acid (1.83 kg) and ethylene glycol (0.9 kg) were transported to a 5L esterification kettle, pressurized to 0.3 MPa, and heated to 220-250°C for esterification reaction under stirring, wherein the stirring speed was 50 rpm. The end point of the esterification reaction was determined by the volume of distilled water, i.e., the end point of the esterification reaction was when 1.1 kg of water was distilled. After the esterification reaction was completed, a titanium catalyst (based on the amount of polyester generated, the weight (mass concentration) of titanium element was 10 ppm) was added to the slurrying kettle for vacuum polycondensation. The vacuuming process was divided into two stages: low vacuum and high vacuum. In the vacuum stage, the temperature in the kettle is controlled at 260-270°C, the stirring speed is 50rpm, the vacuum degree in the reactor is controlled at more than 200Pa, and the duration is 30-60min. Then, the high vacuum stage is entered, in which the temperature in the kettle is controlled at 270-290°C, the stirring speed is 50rpm, the vacuum degree in the reactor is controlled below 50Pa, and the duration is 90-240min. When the current of the stirring motor of the reactor no longer increases or the torque no longer increases, the stirring is stopped, and the melt is pressed out with nitrogen, drawn into strips through a die, cooled in a water tank, and then enters a pelletizer to obtain copolyester chips.

[0097] The obtained copolyester chips were dried and sent for testing. The specific data records are shown in Table 1.

[0098] Table 1:

[0099]

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A titanium-silicon homogeneous polyester catalyst, characterized in that: The titanium-silicon homogeneous polyester catalyst is mainly prepared from a titanium compound, a silicon compound and an organic phosphine ligand of formula (I); In formula (I), R, R', and R" are independently one of -OH, -COOH, -PO3H2, -NO2, -NH2, -SO3H, -H, -H2C-COOH, -H2C-NH2, -H2C-PO3H2, a monocyclic aromatic hydrocarbon group, and a C1-C6 alkane chain structure, and n is an integer of 1 to 8; The monocyclic aromatic hydrocarbon groups include: One of; In the monocyclic aromatic hydrocarbon group, R1 to R5 are independently one of —OH, —COOH, —PO3H2, —NO2, —NH2, —SO3H, —H, —H2C-COOH, —H2C-NH2, —H2C-PO3H2, a monocyclic aromatic hydrocarbon group and a C1-C6 alkane chain structure.

2. The titanium-silicon homogeneous polyester catalyst according to claim 1, characterized in that: The organic phosphine ligand is at least one of 1-hydroxyethylidene-1,1-diphosphonic acid, 1-hydroxybutylidene-1,1-diphosphonic acid, 1-hydroxypropylidene-1,1-diphosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 3-phosphopropionic acid, and (4-hydroxybenzyl)phosphonic acid.

3. The titanium-silicon homogeneous polyester catalyst according to claim 1, characterized in that: The titanium compound is tetraalkyl titanate, and the alkyl ester contained in the tetraalkyl titanate is a C1-C7 alkyl group; Preferably, the tetraalkyl titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.

4. The titanium-silicon homogeneous polyester catalyst according to claim 1, characterized in that: The silicon compound is at least one of ethyl orthosilicate, tetraisopropyl orthosilicate and tetra-n-propyl orthosilicate.

5. A method for preparing a titanium-silicon homogeneous polyester catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (A) providing a titanium compound solution, a silicon compound solution and an organic phosphide ligand solution; (B) adding the organic phosphide ligand solution to the titanium compound solution, stirring the mixture to react and preparing a reaction product I; (C) Adding the silicon compound solution to the reaction product I, stirring the reaction to obtain the reaction product II, and removing the small molecules to obtain the titanium silicon homogeneous polyester catalyst.

6. The method for preparing a titanium-silicon homogeneous polyester catalyst according to claim 5, characterized in that: The mass ratio of the titanium compound to the solvent in the titanium compound solution is 1:0.5-50; And / or, the mass ratio of silicon compound to solvent in the silicon compound solution is 1:0.5-30; And / or, the mass ratio of the organic phosphide ligand to the solvent in the organic phosphide ligand solution is 1:0.5-50.

7. The method for preparing a titanium-silicon homogeneous polyester catalyst according to claim 5, characterized in that: During the preparation of the reaction product I, the molar ratio of the titanium compound to the organic phosphide ligand is 1:0.1-10.

8. The method for preparing a titanium-silicon homogeneous polyester catalyst according to claim 5, characterized in that: During the preparation of the reaction product II, the molar ratio of the titanium compound to the silicon compound is 1 to 20:

1.

9. The method for preparing a titanium-silicon homogeneous polyester catalyst according to claim 5, characterized in that: The reaction temperature of step (B) is 50-120°C and the reaction time is 0.5-4h; The reaction temperature of step (C) is 50-120° C. and the reaction time is 0.5-4 h.

10. Use of the titanium-silicon homogeneous polyester catalyst according to any one of claims 1 to 4 in catalytic preparation of polyethylene terephthalate and its copolyester.